Hepatocyte‐Specific Delivery of siRNAs Conjugated to Novel Non‐nucleosidic Trivalent N‐Acetylgalactosamine Elicits Robust Gene Silencing in Vivo. Issue 6 (18th March 2015) - Rajeev, Kallanthottathil G.; Nair, Jayaprakash K.; Jayaraman, Muthusamy; Charisse, Klaus; Taneja, Nate; O'Shea, Jonathan; Willoughby, Jennifer L. S.; Yucius, Kristina; Nguyen, Tuyen; Shulga‐Morskaya, Svetlana; Milstein, Stuart; Liebow, Abigail; et al.
Abstract We recently demonstrated that siRNAs conjugated to triantennary N‐acetylgalactosamine (GalNAc) induce robust RNAi‐mediated gene silencing in the liver, owing to uptake mediated by the asialoglycoprotein receptor (ASGPR). Novel monovalent GalNAc units, based on a non‐nucleosidic linker, were developed to yield simplified trivalent GalNAc‐conjugated oligonucleotides under solid‐phase synthesis conditions. Synthesis of oligonucleotide conjugates using monovalent GalNAc building blocks required fewer synthetic steps compared to the previously optimized triantennary GalNAc construct. The redesigned trivalent GalNAc ligand maintained optimal valency, spatial orientation, and distance between the sugar moieties for proper recognition by ASGPR. siRNA conjugates were synthesized by sequential covalent attachment of the trivalent GalNAc to the 3′‐end of the sense strand and resulted in a conjugate with in vitro and in vivo potency similar to that of the parent trivalent GalNAc conjugate design.